Competitive intelligence 2.0 : organization, innovation and territory - Quoniam, Luc (ISTE., 2011)
The recent "concept of 2.0"", a consequence of ""Web 2.0"", discusses the emergence of a new style, emancipated from the Web, which finds applications in all areas of social activity: management, innovation, education , organization, territory, etc.This book considers the implications of the changing paradigm for competitive, economic and territorial intelligence applied to innovation, value creation and enhancement of territories. Competitive intelligence is therefore in the ""2.0"" and its values: perpetual beta, user-generated content, social relations, etc., horizontality, a renewed le.